1992
DOI: 10.7164/antibiotics.45.1492
|View full text |Cite
|
Sign up to set email alerts
|

The squalestatins, novel inhibitors of squalene synthase produced by a species of Phoma. III. Biosynthesis.

Abstract: The biosynthetic origin of the carbon and oxygen atoms of the novel fungal secondary metabolite 1 was studied. Incorporation studies with single and multiple labelled 13C precursors indicated that the major portion of the molecule was derived from two polyketide chains madeup of acetate units. One of the chains had benzoic acid (which can be derived from phenylalanine) as a starter unit. The remaining carbons were derived from a four-carbon unit related to succinate and from methionine.Studies with [l-13C,18O2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…The oxidative pathway that converts 2 to 6 determined here is fully consistent with the earlier 18 O 2 feeding experiments 3. Acetylation of 6 at O -9 (Mfr4) then gives 4 which is already known as the substrate for the final acylation reaction catalysed by Mfm4 4.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The oxidative pathway that converts 2 to 6 determined here is fully consistent with the earlier 18 O 2 feeding experiments 3. Acetylation of 6 at O -9 (Mfr4) then gives 4 which is already known as the substrate for the final acylation reaction catalysed by Mfm4 4.…”
Section: Discussionsupporting
confidence: 85%
“…Isotopic feeding experiments using 13 C-labelled acetates show that 1 consists of two polyketides: a benzoate-primed hexaketide, which forms the core moiety; and a dimethylated tetraketide ester side chain. More sophisticated experiments using [1- 13 C]-acetate in combination with 18 O 2 showed that the carbon skeleton of 1 is heavily oxidised during biosynthesis and that oxygens at positions 1, 3, 5, 6, 7 and 12 are derived from atmospheric oxygen (Scheme 1) to form the 4,8-dioxa-bicyclo[3.2.1]octane core 3…”
Section: Introductionmentioning
confidence: 99%
“…C-16 and C-17 were labeled by [2- 13 C]acetate and C-15 and C-18 by [1- 13 C]acetate ( Figure 3 ). This labeling pattern is inconsistent with normal polyketide chain elongation but could be explained by incorporation of succinate, which can be labeled by 13 C-labeled acetates in TCA cycle [ 10 , 11 ]. However, the feeding of 1,4- 13 C 2 -succinic acid gave no signal enhancement for C-15 and C-18 of akaeolide ( Supplementary Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…This shows that the active molecule(s) of A. oryzae CNCM I-2526 inhibited the conversion of lanosterol to lathosterol. This also excludes the class of squalestatins or viridiofungins which inhibit squalene synthase [16,17] (being located upstream of lanosterol) as the active compounds from strain CNCM I-2526. The inhibitory activity was distributed over several fractions (Table 2) and the presence of this activity within fractions of different physico-chemical properties, acting on the same conversion step, suggested the existence of several active molecules.…”
Section: Discussionmentioning
confidence: 99%